The freshwater mollusks (Gastropoda, Pulmonata, Lymnaeidae) from the Pontian sediments of the Southern Ukraine - Kovalenko, V. A. (Reports of the National Academy of Sciences of Ukraine, 2016)
The species distribution data for the Pontian freshwater air-breathing mollusks of the family Lymnaeidae at the Southern Ukraine are generalized. 15 types of Lymnaea belonging to the same genus (Lymnaea Lama r c k, 1771), six subgenera (Lymnaea s. str; Corvusiana S e r v a i n, 1881; Stagnicola Lea c h, 1830; Galba S c h ra n c k, 1803; Peregriana Sevain, 1881; Omphiscola Ra f i - n e s q u e, 18190), eight sections (Lymnaea s. str; Corvusiana s. str; Berlaniana Kr u g l o v e t S t a ro bog a t o v, 1985; Fenziana S e r v a i n, 1881; Galba s. str; Cyphideana S e r v a i n, 1881; Bouchardiana S e r v a i n, 1881; Ampullaceana S e r v a i n, 1881) are recognized in the Lower Pontian (Novorossiysk’s regiosubstage) and Upper Pontian (Bosphorus regiosubstage) deposits of the Southern Ukraine (the Black Sea Lowland; Preddobrudja; Eastern Crimea). It is found that the Upper Pontian Lymnaeidae complex differs from the Lower Pontian one by solely the occurrence of their “current” species.